2017
DOI: 10.1093/bja/aew476
|View full text |Cite
|
Sign up to set email alerts
|

Risk prediction models for delirium in the intensive care unit after cardiac surgery: a systematic review and independent external validation

Abstract: Numerous risk prediction models are available for predicting delirium after cardiac surgery, but few have been directly compared with one another or been validated in an independent data set. We conducted a systematic review to identify validated risk prediction models of delirium (using the Confusion Assessment Method-Intensive Care Unit tool) after cardiac surgery and assessed the transportability of the risk prediction models on a prospective cohort of 600 consecutive patients undergoing cardiac surgery at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 35 publications
1
61
0
Order By: Relevance
“…The variable incidence is due to: different patient baseline characteristics; types of ICU (medical, surgical or both); illness severity; screening tools for diagnosis of delirium; and concomitant medications . Several international studies have suggested a strong association between delirium and short‐term/long‐term mortality . In keeping with previous observational studies , the incidence of delirium in our review was 18.5% in the control group and 7.6% in the dexmedetomidine group, the difference being statistically significant.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The variable incidence is due to: different patient baseline characteristics; types of ICU (medical, surgical or both); illness severity; screening tools for diagnosis of delirium; and concomitant medications . Several international studies have suggested a strong association between delirium and short‐term/long‐term mortality . In keeping with previous observational studies , the incidence of delirium in our review was 18.5% in the control group and 7.6% in the dexmedetomidine group, the difference being statistically significant.…”
Section: Discussionsupporting
confidence: 83%
“…The incidence of delirium varies widely from 16.1% to 83.3% in ICU patients, especially among those undergoing mechanical ventilation (60–80%) . The variable incidence is due to: different patient baseline characteristics; types of ICU (medical, surgical or both); illness severity; screening tools for diagnosis of delirium; and concomitant medications . Several international studies have suggested a strong association between delirium and short‐term/long‐term mortality .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, delirium is associated with excess healthcare costs of more than $164 billion per year . Delirium can be difficult to detect and manage and is receiving greater attention in the medical literature …”
Section: Network For Investigation Of Delirium Across the Us (Nidusmentioning
confidence: 99%
“…1,2 Delirium can be difficult to detect and manage and is receiving greater attention in the medical literature. [3][4][5] A number of factors, including cognitive impairment, infection, dehydration, and psychoactive medications, are predictive of delirium. 2 In most cases, delirium is multifactorial, which makes finding effective approaches for prevention and treatment highly challenging and research studies methodologically complex.…”
mentioning
confidence: 99%
“…Knowledge of, particularly modifiable, risk factors for POD and POCD is therefore imperative to enhance informed patient consent, adjust anesthetic and surgical strategies to individual risk profiles and facilitate appropriate postoperative monitoring (30). Numerous risk prediction models have been developed, yet recent studies highlight that a general application of these models in clinical routine is limited, not least because trajectories of cognitive decline are not independent of the type of surgery (20,24,31,32). For example, patients who exhibited POCD following cardiac surgery improved cognitive function after one year compared to their baseline level, which contradicts results from mixed surgical populations (24,32).…”
Section: Introductionmentioning
confidence: 99%